Desafios na Pesquisa de Leitura, Escrita, Interpretação e Tradução: Uma Homenagem a Márcia Schmaltz (1973*-2018†) - Da Silva, Igor Antônio Lourenço; Ferreira, Aline; Schwieter, John W. (Domínios de Lingu@gem, 2019)
Apresentação